2014
DOI: 10.1007/s10995-013-1253-6
|View full text |Cite
|
Sign up to set email alerts
|

Overweight, Gestational Weight Gain and Elevated Fasting Plasma Glucose and Their Association with Macrosomia in Chinese Pregnant Women

Abstract: To provide a current estimation of overweight, gestational weight gain(GWG), elevated fasting plasma glucose (FPG) in pregnant women in Kunshan, China and investigate their association with macrosomia using recommendations of IOM and International Association of Diabetes and Pregnancy Study Groups. We conducted a population-based retrospective study and analyzed routine data from Kunshan Maternity and Child Care Surveillance System of 27,322 women with singleton full-term birth from 2006 to 2010. The prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 17 publications
0
19
0
2
Order By: Relevance
“…The study by Cedergren showed that both elevated pre‐pregnancy weight and excess weight gain conferred risks of fetal macrosomia In the Chinese population, because of the lower prevalence of high maternal BMI compared with developed countries, being overweight or obese does not seem to be the most important contributor to macrosomia. However, obesity has been increasing in recent years . Thus, in the future how to encourage overweight or obese women to get healthy pre‐pregnancy weights and limit excessive weight gain during pregnancy needs more attention from health care providers.…”
Section: Commentmentioning
confidence: 99%
“…The study by Cedergren showed that both elevated pre‐pregnancy weight and excess weight gain conferred risks of fetal macrosomia In the Chinese population, because of the lower prevalence of high maternal BMI compared with developed countries, being overweight or obese does not seem to be the most important contributor to macrosomia. However, obesity has been increasing in recent years . Thus, in the future how to encourage overweight or obese women to get healthy pre‐pregnancy weights and limit excessive weight gain during pregnancy needs more attention from health care providers.…”
Section: Commentmentioning
confidence: 99%
“…Macrosomia, defined as a birthweight of more than 4000 g regardless of gestational age, has risen markedly and has become a major public health concern worldwide (including China) throughout the past two decades . A recent hospital‐based, cross‐sectional survey in China reported a prevalence of macrosomia as high as 13.4% in some areas .…”
mentioning
confidence: 99%
“…Fetal makrozomi riskini arttıran durumlar, önceki çalışmalarda, ileri anne yaşı [4], gebelik öncesi obezite, gebelikte fazla kilo alımı olarak tespit edilmiştir [1,[6][7][8]. Ülkemizde ve Tunus'ta yapılan iki çalışmada, gebelik öncesi VKE arttıkça makrozomik bebek doğurma olasılığının arttığı gösterilmiştir [9,10].…”
Section: Discussionunclassified
“…İran'da ve Çin'de yapılan gestasyonel diyabetli gebeleri hariç tutan iki çalışmada da açlık kan glukozu düzeyleri makrozomik bebek doğuran grupta belirgin olarak yüksek bulunmuştur [8,15]. Ülkemizde yapılan bir araştırma sonucunda, ikinci trimesterdeki 50 gram oral glukoz yüklemesi sonrası 1. saat kan glukoz düzeyleri 130 ile 140 mg/ dL arası olan hastalarda makrozomiyi öngörmede önemli göstergeler, makrozomik doğum öyküsü ve 29-34 gebelik haftaları arasında ölçülen fetal karın çevresi değerleri olarak bulunmuştur [26].…”
Section: Wwwjceionlineorgunclassified